From Democratic Participation to School Choice: Quasimarket Principles in the Spanish Educational Legislation - Olmedo Reinoso, Antonio (Education Policy Analysis Archives, 2008)
This paper is part of a broader research project that aims to study and give some theoretical explanation to the inclusion/exclusion dynamics produced by the application of neoliberal policies in education. It focuses on those policies that promote school choice and family involvement. The goal was to contextualize the role of the State over these issues, analyzing the legislative framework in which families act and take decisions in relation to their children's education process. Far from trying to give a mere description of the contents of those policies, this article tries to understand and point out their possible effects in comparison with other contexts that have already developed similar dynamics. The article suggests that the trajectory of the Spanish educational policy over school choice and participation has redefined the role of families in relation to their children's schooling process. The result has been the transition from an active role in the daily organization and management of the schools to another one more specific and restricted where the families could be defined as consumers of education focusing on the control through choice of those schools that are considered as the "best and more appropriate" in order to fulfil present and future aspirations and expectations.